The correlations of adverse effect and tonifying effect of ginseng medicines. (12th June 2022) - Ran, Xiaoku; Dou, Deqiang; Chen, Hongyu; Ren, Guoqing
Abstract: Ethnopharmacological relevance: Ginseng has been used for thousands of years, it is described as both a tonic for restoration of strength and a panacea. However, the adverse effect is also reported clinically. In the theory of Traditional Chinese Medicine, the occurrence of adverse reactions is closely related to warm property of ginseng, which can easily lead to fireness (火, in Chinese). Several presumptions indicated that fireness of ginseng may be associated with the pathophysiology of inflammation, imbalance of metabolism, the disorder of hypothalamus-pituitary-adrenal axis, and hypothalamus-pituitary-thyroid axis. Aim of the study: The tonifying effect of ginseng medicines was always focused on with little attention for their adverse effects. We selected red ginseng (RG), ginseng (GS), American ginseng (AG), and ginseng leaves (GL) as typical ginseng medicines to clarify correlations of adverse effect and tonifying effect of ginseng medicines. Materials and methods: The RG, GS, AG, and GL decoctions were orally administered to rats for 30 days consecutively. The appearance indicators such as saliva secretion, urinary output, fecal moisture, heart rate were determined, and hair condition, nose color were also observed. Furthermore, some biochemical indexes such as IL-6, T3, T4, TSH, ACTH, CORT, Ach, DA, EPI, NE, SP, VIP, cAMP, cGMP, AQP-5, AMPK, and the activity of SOD, GSH-PX, Na + -K + -ATPase were measured by biochemical reagent kits or enzyme-linked immunosorbent assay (ELISA). The metabolites profile was analyzed by UPLC-QTOF-MS. Finally, the diversity of gut microbiota was also analyzed with the 16S rDNA sequencing. Results: The study revealed the tonifying effects of ginseng medicines mainly on exciting nervous system, promoting immunity and antioxidative ability. While, the adverse effects were mainly associated with the abnormal nervous system, thyroid system, adrenal system, and oxidative stress. The GS group showed fireness symptoms, such as vertical and dirty hair, epistaxis, higher rectal temperature, lower salivary secretion, lower urinary output, lower fecal moisture. While the GL group showed the opposite symptoms. The levels of hormones, activities of the antioxidative enzyme, and Na + -K + -ATP enzyme were changed differently. From the second week to the fourth week, the levels of T3, T4, TSH, ACTH, CORT, and the activity of SOD, GSH-PX, Na + -K + -ATP enzymes were first increased, then decreased, and finally recovered to normal levels. We also found that the ginseng medicines mainly adjust the amino acid and TCA cycle metabolism exhibiting their tonifying and adverse effects. Meanwhile, GS and AG can modulate gut microbiota imbalance by increasing the gut microbial diversity as well as selectively promoting some probiotic populations, including Lactobacillus and Bifidobacterium . Conclusions: This is the first time to report the correlations between tonifying effects and adverse effects of four ginseng medicines. The present study demonstrated that the adverse effects of ginseng medicines mostly depended on their dosages, the higher dosage is, the more serious the adverse effects are. The adverse effects of ginseng and ginseng leaves are much more serious than red ginseng and American ginseng. The tendency of water regulation of ginseng and ginseng leaves was opposite may be related to their nature property. Graphical abstract: Image 1 Highlights: Ginsengs as the most tonic medicines have been widely concerned by people, and their adverse effect have been ignored. We discussed the dynamic changes of rats treated with different ginsengs in different periods. The tonic effects and adverse effects were referred to various systems, such as the nervous system, HPT and HPA axis system. Ginseng medicines showed different degrees of tonifying effects and different adverse effects at different periods. The adverse effects were mild and reversible, and the animals could easily recover from the adverse effects conditions.